Therapeutic Properties of Mesenchymal Stem Cell on Organ Ischemia-reperfusion Injury: A Review - Oliva, Joan (Recent Research Advances in Biology Vol. 10, 2021)
The shortage of donor organs is a major global concern. Organ failure requires the transplantation of functional organs. Donor’s organs are preserved for variable periods of warm and cold ischemia time, which requires placing them into a preservation device. Ischemia and reperfusion damage the organs, due to the lack of oxygen during the ischemia step, as well as the oxidative stress during the reperfusion step. Different methodologies are developed to prevent or to diminish the level of injuries. Preservation solutions were first developed to maximize cold static preservation, which includes the addition of several chemical compounds. The next chapter of organ preservation comes with the perfusion machine, where mechanical devices provide continuous flow and oxygenation ex vivo to the organs being preserved. In the addition of inhibitors of mitogen-activated protein kinase and inhibitors of the proteasome, mesenchymal stem cells began being used 13 years ago to prevent or diminish the organ’s injuries. Mesenchymal stem cells (e.g., bone marrow stem cells, adipose derived stem cells and umbilical cord stem cells) have proven to be powerful tools in repairing damaged organs. This review will focus upon the use of some bone marrow stem cells, adipose-derived stem cells and umbilical cord stem cells on preventing or decreasing the injuries due to ischemia-reperfusion.